Effect of Application of Nitrogen Fertilizer, Microbial and Humic Substance-Based Biostimulants on Soil Microbiological Properties During Strawberry (Fragaria × ananassa Duch.) Cultivation - Maková, Jana; Artimová, Renata; Javoreková, Soňa; Adamec, Samuel; Paulen, Oleg; Andrejiová, Alena; Ducsay, Ladislav; Medo, Juraj (Horticulturae, 2025)
Plant biostimulants have been the subject of intense interest in recent years. The aim of this study was to assess, during the years 2021–2022, the effect of mineral nitrogen (N) fertilizer, experimental (PGPB) and commercial (G) microbial biostimulants, and humic substance product (A) on the soil microbial communities, and yield of strawberries, under field conditions. Dehydrogenase activity was significantly affected by nitrogen fertilization, but an increase occurred in the treatment N+G. The treatments N+G, N+G+A, and N+PGPB+A increased FDA hydrolysis, and phosphatase activity. All plant biostimulants increased basal as well as substrate-induced respiration. Culturable bacteria (total counts, dormant forms, actinomycetes) were not clearly affected by treatment. Based on 16S rRNA analysis, bacterial community composition was different in N+PGPB+A and N+G+A treatments. The number of cultivable fungi was significantly lower in N+PGPB and N+PGPB+A treatments. The genus of fungi Pilidium, a potential phytopathogen of strawberries, was present in the second year, but in these treatments, it was absent. In the second year, strawberry yield was shown to be 95% higher in the N+PGPB+A treatment than in the control. Microbial biostimulants in combination with humic substances represent a potential solution in increasing strawberry production.